A new cross‐linked system of silicone rubber based on silicone‐polyurea block copolymer. (1st May 2018) - Liu, Yuetao; Zhu, Dan; Sun, Jiawen; Wu, Yumin; Gao, Chuanhui
Abstract : A new cross‐linked system of silicone rubber (SR) was obtained from silicone‐polyurea block copolymers that was synthesized with aminopropyl terminated polydimethylsiloxane and (4‐isocyanatocyclohexyl)‐methane. SR possessed self‐reinforced and physical cross‐linked structure. It had better mechanical properties that the hardness, the tensile strength, and the elongation at break could reach 65 Shore A, 3.78 MPa, and 458% with the polyurea segment content ranging from 2.01% to 9.13% by weight. The hydrogen bond that led to the physical cross‐linked structure was proved byFourier transform infrared spectroscopy. The microphase separated structure that caused the self‐reinforcement was illustrated by scanning electron microscopy, X‐ray diffraction analysis, and dynamic mechanical analysis. Fourier transform infrared spectroscopy results showed the hydrogen bond formation between the polyurea units. Scanning electron microscopy, dynamic mechanical analysis, and X‐ray diffraction analysis results proved the microphase separation existed between polyurea units and ―Si―O―Si― chains. The increase of polyurea contents enhanced the binding of hydrogen bond and improved the extent of microphase separation. Accordingly, it decreased the thermal properties and lowered the glass transition temperature ( T g ) from −108°C to −114°C. Also, the increase of polyurea contents increased the hydrophobicity of SR that the surface free energy could reach to −24.81 mN/m.